Reconstruction of Supervision in Online Trial as Evaluated Review During the Covid-19 Pandemic - Sriwidodo, Joko (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
The various problems encountered during online trials highlight an impaired supervision mechanism. This research is part of a need for a reconstruction in the supervision of online trials in Indonesia. Therefore, the formulation of the problem is: What are the problems that arise in online trials during the Covid-19 pandemic? How can the reconstruction of supervision in these trials be carried out? Furthermore, a descriptive, normative method was applied alongside a qualitative, statute approach. The results showed that problems related to the supervision of online trials include the absence of clear legal rules and procedures that have not been regulated in Indonesia Law. It is necessary to supervise judges during these trials, and this supervision has not involved the Indonesian judicial system, specifically the Judicial Commission or KY. Therefore, there is a need for reconstruction in supervision through the Revision of the Criminal Procedure Code (KUHAP), the Establishment of Special Regulations Related to the Online Trial Law, and the Formation of a Special Team for Online Trial Supervisors.